ISLAM NUSANTARA: AMBIGUITY, CULTURAL STRATEGY OR ORIGINALITY : (A Historical Studies) - Abdul Aziz; Debi Arlianto (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2023)
Islam Nusantara is a new term in Indonesia. The opposing group views it as a form of Islamic division, and the pro group considers it a strategy for Islamic da'wah with a slogan of moderation and a cultural approach. Islam Nusantara is defined as Islam that is friendly, inclusive, dynamic, and friendly with a diverse cultural, sub-cultural and religious environment. From this meaning, the question arises from this ambiguity: